Separation of squalene from olive oil deodorizer distillate using supercritical fluids - Akgun, Nalan A. (WILEY, 2011)
In this study, an integrated strategy using supercritical fluids for extraction of squalene from olive oil deodorizer distillate (OODD), one of the most important by-products of the olive oil refining process is presented. First, OODD was esterified in supercritical methanol, and then squalene was extracted from the sample consisting of 66% methyl ester using supercritical CO2. The extraction conditions, i.e., pressure (88.2-121.8 bar), temperature (41.6-58.4 degrees C) and extraction time (129.6-230.4 min), were optimized via RSM to achieve the highest squalene content. The optimal results were obtained at a temperature of 52.05 degrees C, pressure of 104.8 bar and extraction time of 180 min. Consequently, two kinds of value-added products such as biodiesel (up to 96% FAME, in extract) and olive squalene (up to 75%, in raffinate) were produced in shorter processing times when compared with distillation results of 70 h.
Keywords: Deodorizer distillate; Response surface methodology; Squalene; Supercritical carbon dioxide extraction; Supercritical methanol esterification; PHASE-EQUILIBRIA; CARBON; EXTRACTION; DIOXIDE; ADSORPTION; TOCOPHEROL; RECOVERY; Food Science & Technology; Nutrition & Dietetics